2021
DOI: 10.3390/ma14143955
|View full text |Cite
|
Sign up to set email alerts
|

Tailings after Iron Extraction in Bayer Red Mud by Biomass Reduction: Pozzolanic Activity and Hydration Characteristics

Abstract: Bayer red mud (BRM) is a kind of solid waste with high hematite content, and its effective utilization is difficult due to the special physicochemical properties. In this work, Fe2O3 in BRM was reduced to Fe3O4 by biomass, and iron concentrate and high activity tailings were obtained after magnetic separation. The pozzolanic activity and hydration characteristics of the tailings were systematically studied. The results showed that the relatively stable polymerization structures of Si-O and Al-O in BRM are dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is well known that cement hydration can generate large amounts of Ca(OH) 2 , but Ca(OH) 2 was not found in the XRD pattern. This means that the Ca(OH) 2 has been consumed by the pozzolanic activity of slag and red mud [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that cement hydration can generate large amounts of Ca(OH) 2 , but Ca(OH) 2 was not found in the XRD pattern. This means that the Ca(OH) 2 has been consumed by the pozzolanic activity of slag and red mud [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The phase composition has an important influence on the pozzolanic activity of RM. Previous studies have shown that the amorphous phase is the most active phase in supplementary cementitious materials, such as GGBFS and fly ash [ 3 ]. The XRD patterns of RM calcined at different temperatures, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the FTIR spectra of RM calcined at different temperatures. The absorption peak is 3638 cm −1 , which corresponds to the stretching vibration of free –OH [ 3 ]. The absorption peak at 3452 cm −1 corresponds to the stretching vibration of associating –OH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations